Perbandingan Hasil Belajar Siswa Melalui Model Pembelajaran TGT Dan STAD Pada Mata Pelajaran Ekonomi - Deti Setiawati; Ai Nur Solihat; Astri Srigustini (JURNAL ILMIAH NUSANTARA, 2025)
The problem in this study is caused by the low learning outcomes of students. The purpose of this study to improve student learning outcomes in economics subjects by using the Teams Games Tournament (TGT) and Student Teams Achievement Division (STAD) learning models in class XI of SMAN 4 Tasikmalaya. The method used is quantitative with a quasi-experimental type with a pre-test post-test nonequivalent multiple group design research design. The population used in this study were all class XI taking economics with a total of 108 students, while the sample used was class XI-7 and XI-10 with sampling using a nonprobability sampling technique of the purposive sampling type. The result showed that there were differences in improving student learning outcomes using the Teams Games Tournament (TGT) and Student Teams Games Tournament (STAD) learning models which can be seen from the result of the pre-test and post-test as well as the result of data processing using SPSS. The result prove that both learning models can improve student learning outcomes in economics subjects with the material of price index and inflation in class XI SMAN 4 Tasikmalaya. This study concludes that experimental class 2 using the Student Teams Achievement Division (STAD) learning model experienced a higher increase in learning outcomes compared to experimental class 1 using the Teams Games Tournament (TGT) learning model.